2020
DOI: 10.3390/antibiotics9120872
|View full text |Cite
|
Sign up to set email alerts
|

Do Prosthetic Joint Infections Worsen the Functional Ambulatory Outcome of Patients with Joint Replacements? A Retrospective Matched Cohort Study

Abstract: Objectives: To assess the effect on the functional ambulatory outcome of postoperative joint infection (PJI) cured at the first treatment attempt versus not developing PJI in patients with hip and knee prostheses. Methods: In a single-hospital retrospectively matched cohort study, each patient with PJI between 2007 and 2016 was matched on age, sex, type of prosthesis and year of implantation with two other patients with uninfected arthroplasties. The definition of a PJI cure included infection eradication, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Six of the eight studies ( 3 , 15 , 16 , 17 , 19 , 20 ) assessed the patients’ post-surgical joint pain and function using an appropriate joint function tool (ambulatory outcomes, OHS, OKS, HHS, or WOMAC). Wildeman et al ( 3 ) and Mur et al ( 20 ) reported a greater proportion of PJI patients requiring ambulatory aids and assisted living relative to uninfected patients ( Table 2 ). Wildeman et al ( 3 ) identified a worse OHS score in PJI patients.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…Six of the eight studies ( 3 , 15 , 16 , 17 , 19 , 20 ) assessed the patients’ post-surgical joint pain and function using an appropriate joint function tool (ambulatory outcomes, OHS, OKS, HHS, or WOMAC). Wildeman et al ( 3 ) and Mur et al ( 20 ) reported a greater proportion of PJI patients requiring ambulatory aids and assisted living relative to uninfected patients ( Table 2 ). Wildeman et al ( 3 ) identified a worse OHS score in PJI patients.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…In contrast to the treatment of other infections, the goal of orthopedic implant-associated infection treatment is not only to eradicate the infection but also to relieve pain and maintain joint function. , Orthopedic implant-associated infection impairs the patient’s walking ability, which is caused by the pain and osteolysis resulting from the infection . Since fenoprofen is an NSAID with analgesic effects and can control implant-associated infection, we analyzed the effects of fenoprofen on the walking ability of mice with implant-associated osteomyelitis.…”
Section: Resultsmentioning
confidence: 99%
“…47,48 Orthopedic implant-associated infection impairs the patient's walking ability, which is caused by the pain and osteolysis resulting from the infection. 49 Since fenoprofen is an NSAID with analgesic effects and can control implant-associated infection, we analyzed the effects of fenoprofen on the walking ability of mice with implantassociated osteomyelitis.…”
Section: Fenoprofen Has Potent Antivirulence Efficiency By Inhibiting...mentioning
confidence: 99%
“…Del Toro et al demonstrated that 71% of patients who underwent HA and developed PJI had poor function, compared with 30% of patients who underwent THA 45 . In another series, PJI after hip HA was associated with an increased probability of using 2 crutches or being unable to walk independently (OR, 3.05 [95% CI, 1.01 to 9.20]; p = 0.047) compared with patients who developed PJI after THA 109 . Short-term mortality and long-term mortality are also markedly increased in this population.…”
Section: Outcomes Following Pji After Hip Hamentioning
confidence: 95%